Exposing Pelaku Bid and Run Pada Lelang Online Di Instagram Oleh Akun @gordonauction.Id; Studi Komparatif Antara UU ITE Dan Hukum Islam - Ibadurrahman Zaqi (Wasathiyyah, 2023)
In today's digital era, online auctions on platforms such as Instagram have become increasingly popular, offering convenience but also posing risks, including fraud, such as the